Towards an integrated management of human and animal waste in Viet Nam: Regulation and health and environmental impacts - Nguyen Kim Ngan; Nguyen Ngoc Bich; Phuc Pham Duc; Vu Van Tu; Schelling, E.; Hung Nguyen-Viet (2013)
Untreated human and animal excreta once being released into the environment can be a hazard to the environment and human health by possible pathogens and drug residues. Integrated human and animal manure management faces challenges given that livestock is kept in proximity to human residencies and large amounts of human and animal manure are produced in limited space. Meanwhile the demand of livestock and humans manure reuse in agriculture and fisheries requires that the hygienic safety of both treated human and animal excreta is ensured and their nutrient contents remain high. This research aims to assess the situation of human and animal excreta management based on regulation documents and environmental health impact approaches and to introduce some initial researches on integrated animal and human waste management. Finally, recommendations on human and animal waste management to reuse the excreta safely and effectively are provided.